Analysis of Adjacency Pairs in the Conversations of the Movie Spider-Man: Into the Spider-Verse - Vananda, I Putu Yona; Kasni, Ni Wayan; Muliawan, Made Sani Damayanthi (Austronesian: Journal of Language Science & Literature, 2026)
This study examines adjacency pairs in the conversations of the animated movie Spider-Man: Into the Spider-Verse (2018). The study focuses on identifying the types of adjacency pairs and explaining their interactional functions in the dialogue. This research applies a descriptive qualitative method using movie dialogue and official script as data sources. Data were collected through observation and note-taking and analyzed using Conversation Analysis by Schegloff and Sacks (1973), Preference Organization by Levinson, and discourse analysis by Paltridge (2012). The findings show ten adjacency pair types, namely question–answer, request–acceptance, request–refusal, assessment–agreement, assessment–disagreement, greeting–greeting, offer–acceptance, offer–refusal, apology–acceptance, and compliment–acceptance. The question–answer pattern appeared most dominantly because many interactions demanded clarification from Miles. Adjacency pairs not only regulate the order of conversation but also indicate power relations and emotional states. The results indicate that adjacency pairs organize turn-taking, reveal power relations, express emotional pressure, and support character development. Miles Morales appears as a reactive participant who gradually becomes confident and independent through interaction patterns. Changes in response patterns indicate character development. Miles initially avoids, gives minimal answers, and uses indirect refusals. As the story progresses, he gives acceptance, agreement, and clearer responses. Nonverbal responses such as silence, nods, and facial expressions also function as part of the conversation pair and reinforce the meaning of the interaction. The study concludes that adjacency pairs function as a linguistic mechanism shaping conversational flow and narrative meaning in animated movie dialogue.